Pengaruh Social Media Influencer terhadap Minat Beli Konsumen Di Media Sosial - Hersa Muhammad Cahya (CV. Syntax Corporation Indonesia, 2022)
This study aims to determine and analyze the effect of advertising disclosure on source trust in social media, identify and analyze the effect of advertising disclosure on source expertise on social media, identify and analyze the effect of advertising disclosure on consumer buying intentions on social media, identify and analyze the influence of source trust. on consumer purchase intentions on social media, and knowing and analyzing the influence of source expertise on consumers' purchase intentions on social media. The sample taken is some of the active users of social media. The number of samples in this study is a minimum of 170 active users of social media. Test method and data analysis using SEM-AMOS. The results of this study indicate that advertising disclosure has a significant positive effect on trustworthiness, advertising disclosure has a significant positive effect on expertise, advertising disclosure has a significant positive effect on purchase intention, trustworthiness has a significant positive effect on purchase intention, and expertise has a significant positive effect on purchase intention.